Thioguanine Induces Apoptosis in Triple-Negative Breast Cancer by Regulating PI3K–AKT Pathway - Zhang, Daoyu; An, Xinglan; Li, Qi; Man, Xiaxia; Chu, Meiran; Li, Hao; Zhang, Nan; Dai, Xiangpeng; Yu, Hao; Li, Ziyi (Frontiers in Oncology, 2020)
Triple-negative breast cancer (TNBC) is notoriously difficult to treat due to the lack of biological targets and poor sensitivity to conventional therapies. Chemotherapy is the main clinical therapy, but the effective screening strategy for chemotherapy drugs are poor investigated. Drug repurposing has been the center of attention in recent years attracting numerous studies to develop specific inhibitors. Here, we firstly found multiple common features between leukemia and TNBC by analyzing the global transcriptome profiles based on the transformed comparison data from NCI60. Therefore, we investigated the role of the classic leukemia drug thioguanine (6-TG) in TNBC cancer cells. Our results indicated that 6-TG inhibited cell proliferation and tumor cell progression by suppressing PI3K-AKT pathway via downregulating the DNA methylation level of PTEN. Moreover, apoptosis was induced via the activation of PI3K-AKT downstream TSC1 and the downregulation of methylation levels of DAXX, TNF, FADD and CASP8 etc. These finding indicated 6-TG exerts its anti-tumor effects in vitro and in vivo through regulating the DNA methylation levels of genes involved in PI3K-AKT and apoptosis pathway. Meanwhile, our study suggested that transcriptome-based drug screening has potential implications for breast cancer therapy and drug selection.